School Financing Management In Improving The Quality Of Islamic Education - Adinda, Charisma; Patimah, Hj. Siti (Riviera Publishing, 2023)
Talking about the quality of education will be directly related to the role of schools as educational institutions. Teaching and learning management in schools is very important in determining student success. To achieve good school quality, education costs must be managed optimally. Therefore, the stages in education financing management need to be considered. Basically, the aim of education financing management is to implement an educational process that is in accordance with the expected learning needs of students. This research process uses qualitative research methods. Data collection techniques were carried out by means of observation, documentation and direct interviews with sources. Schools as one of the institutions that carry out educational activities are a production process that produces quality graduates, so financing management is needed so that the quality of graduates can compete to obtain a decent life in society. Management of funds or educational costs at an institution must be able to improve the quality of graduates and be able to compete with other schools based on the principles of justice, efficiency, transparency and public accountability. The results of this research show that education financing management must be implemented optimally starting from financing planning, budgeting, financing implementation, monitoring and controlling financing as well as responsibility or accountability. So that the educational process is implemented in accordance with the expected learning needs of students. So it can be concluded that the management of teaching and learning in schools is very important in determining student success. To achieve good school quality, education costs must be managed optimally.